문화예술 취향 레퍼토리 구조 연구 - 전범수(Bum Soo Chon) (한국콘텐츠학회 논문지, 12(6), 2012)
This study examines the structure of taste repertoires for cultural arts. The major results are as follows: firstly, the numbers of taste repertoires were 1.66 for type 1 and 4.27 for type 2. More specifically, respondents tended to have movie taste. Secondly, there were socio-demographic differences for taste repertoires for cultural arts. In other words. female respondents to have more taste repertoires than that of male respondents. Also, younger respondents to have more taste repertoires than that of older respondent. Thirdly, blog users tended to have more taste repertoires than that of non-users. It can be argued that blog use may be a determinant of the number of taste repertoires for cultural arts. In addition, although the number of taste repertoires type 1 was determined by tastes for theatre, movie, popular music, musical and photo, the number of taste repertoires type 2 was determined by tastes for theatre, movie, musical and classic contents. 본 연구는 기존 텔레비전 연구에서 활용된 레퍼토리 개념을 통해 문화예술 콘텐츠를 선택하는 방식을 구체적으로 탐색했다. 본 연구의 주요 결과는 다음과 같다. 첫째, 문화예술 분야 레퍼토리 비율을 개인별 문화 서비스 레퍼토리로 환산하여 계산한 결과, 레퍼토리 1은 평균 1.66개, 레퍼토리 2는 평균 4.27개로 나타났다. 이들 레퍼토리는 영화 취향을 중심으로 수직적으로 구성되어 있다. 둘째, 인구사회 요인별로 레퍼토리 개수를 살펴본 결과, 레퍼토리 1의 경우에는 성별, 연령, 소득 모두에서 집단 간 차이가 유의미한 것으로 나타났다. 레퍼토리 2도 유사하게 차이가 나타났다. 셋째, 레퍼토리가 전혀 없는 응답자와 1개 이상인 응답자를 구분하는 요인으로 연극, 영화, 뮤지컬 등의 취향이 중요한 역할을 차지하는 것으로 나타났다. 본 연구를 통해 응답자들이 갖고 있는 레퍼토리는 대체적으로 영화와 연극 등 대중문화 중심적인 것으로 나타났다. 반면, 클래식이나 무용, 미술전시회 등의 순수 문화예술 분야에 대한 취향은 응답자별로 분산되는 것으로 나타났다. 반면, 레퍼토리 2를 분석할 때, 순수 문화예술 분야에 대한 취향 정도가 적지 않은 만큼 적극적인 마케팅 및 홍보가 뒷받침된다면 시장을 확대할 수 있는 가능성이 높을 것으로 판단된다.